2009
DOI: 10.1182/blood-2008-07-170282
|View full text |Cite
|
Sign up to set email alerts
|

The preferentially expressed antigen in melanoma (PRAME) inhibits myeloid differentiation in normal hematopoietic and leukemic progenitor cells

Abstract: The preferentially expressed antigen in melanoma (PRAME) is expressed in several hematologic malignancies, but either is not expressed or is expressed at only low levels in normal hematopoietic cells, making it a target for cancer therapy. PRAME is a tumor-associated antigen and has been described as a corepressor of retinoic acid signaling in solid tumor cells, but its function in hematopoietic cells is unknown. PRAME mRNA expression increased with chronic myeloid leukemia (CML) disease progression and its de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 41 publications
0
72
0
8
Order By: Relevance
“…In support of this suggestion, expression studies revealed that BCR-ABL1 dramatically perturbs the CML transcriptome (31), resulting in altered expression of genes, some of which (e.g., PRAME, MZF1, EVI-1, WT1, and JUN-B) might play a role in BP (19,(32)(33)(34). Nonetheless, the posttranscriptional, translational, and posttranslational effects of high BCR-ABL1 levels result in the constitutive activation of factors with reported mitogenic, antiapoptotic, and antidifferentiation activity (e.g., MAPK ERK1/2 , MYC, JAK2, YES-1, LYN, hnRNP-E2, MDM2, STAT5, BMI-1, and BCL-2) and inhibition of major key regulators of cellular processes, such as those regulated by the tumor suppressors p53, CCAAT/enhancer binding protein-α (C/EBPα), and PP2A (19,29,35).…”
Section: Biological Complexity Of Cml-bpmentioning
confidence: 96%
“…In support of this suggestion, expression studies revealed that BCR-ABL1 dramatically perturbs the CML transcriptome (31), resulting in altered expression of genes, some of which (e.g., PRAME, MZF1, EVI-1, WT1, and JUN-B) might play a role in BP (19,(32)(33)(34). Nonetheless, the posttranscriptional, translational, and posttranslational effects of high BCR-ABL1 levels result in the constitutive activation of factors with reported mitogenic, antiapoptotic, and antidifferentiation activity (e.g., MAPK ERK1/2 , MYC, JAK2, YES-1, LYN, hnRNP-E2, MDM2, STAT5, BMI-1, and BCL-2) and inhibition of major key regulators of cellular processes, such as those regulated by the tumor suppressors p53, CCAAT/enhancer binding protein-α (C/EBPα), and PP2A (19,29,35).…”
Section: Biological Complexity Of Cml-bpmentioning
confidence: 96%
“…A previous transcriptome comparison found the expression of testis-cancer antigen PRAME as the discriminative marker of DS AMKL compared with DS TMD, 44 and the overexpression of this gene is known to be due to demethylation of the regulatory regions and is established as a potential driver event in tumorigenesis 52 and inhibitor of differentiation in myeloid leukemic precursor cells. 53 Interestingly, overexpression of PRAME was found to be part of the progression program for CML, in synergy with deregulation of the WNT/b-catenin pathway. 54 In conclusion, our data demonstrate that DS AMKLs form by accumulation of multiple somatic SCNAs and point mutations in genes known as drivers of leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…36 PRAME acts as a 'natural' antagonist of the retinoic acid (RA) receptor and disrupts its downstream signaling, thereby preventing normal RA-induced differentiation. 36 Oehler et al 48 have demonstrated the potential involvement of PRAME in the differentiation arrest that accompanies the conversion of chronic phase CML to blast crisis. 48 A similar observation has been recently made for MUC1.…”
Section: Differentiationmentioning
confidence: 99%
“…36 Oehler et al 48 have demonstrated the potential involvement of PRAME in the differentiation arrest that accompanies the conversion of chronic phase CML to blast crisis. 48 A similar observation has been recently made for MUC1. 49 Finally, accumulating evidence also suggests a critical role for the downregulation of WT1 in the process of myeloid differentiation (reviewed in Yang et al 15 and Sugiyama et al 16 ).…”
Section: Differentiationmentioning
confidence: 99%